2022
DOI: 10.56825/bufbu.2022.4112512
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and therapeutic management of oral tumours in Murrah buffaloes

Abstract: The present study was conducted on eleven Murrah buffaloes suffering from tumourous growth in oral cavity to evaluate the efficacy of surgical and chemotherapeutic treatment along with diagnosis by clinical, radiography and histopathological examination. Radiographic examination was done to observe the invasiveness of tumour, osteolytic changes, teeth displacement, calcification, or any other changes to undertake surgery accordingly. Histopathological examination revealed that all oral tumours were benign in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Alkaline pH of cervical mucus in repeat breeder crossbred cows than the normal cyclic cows has also been reported in cross bred [23] Kankrej [13] and Deoni cows [24]. A significant decline in cervical mucus pH of repeat breeder cows after the treatment with various antibiotics, lugol's and alcoholic extract of neem bark is evident from the earlier studies [25]; Kumar et al, 2013 and Palanisami et al [26]. However, a non significant decline was observed in repeat breeder cross bred cows following their treatment with ceftiofur.…”
Section: Hydrogen Ion Concentration (Ph)mentioning
confidence: 57%
“…Alkaline pH of cervical mucus in repeat breeder crossbred cows than the normal cyclic cows has also been reported in cross bred [23] Kankrej [13] and Deoni cows [24]. A significant decline in cervical mucus pH of repeat breeder cows after the treatment with various antibiotics, lugol's and alcoholic extract of neem bark is evident from the earlier studies [25]; Kumar et al, 2013 and Palanisami et al [26]. However, a non significant decline was observed in repeat breeder cross bred cows following their treatment with ceftiofur.…”
Section: Hydrogen Ion Concentration (Ph)mentioning
confidence: 57%
“…Luktuke and Sharma (1978) [9] supported our finding, he found that high incidence of repeat breeding and anoestrus are associated with the deficiencies of cholesterol might be due to inadequate availability of metabolites and metabolic hormones in the central nervous system causing low level of GnRH secretion from the hypothalamus and also the gonadotrophic hormones from the anterior pituitary gland. Kumar and Saxena, (2010) [8] recorded high plasma total cholesterol concentration in normal cyclic than the repeat breeder cows. Though there was no significant difference in the levels between conceived and non-conceived groups.…”
Section: F Cholesterol (Mg/dl)mentioning
confidence: 93%
“…The loss of ovarian activity in hypoglycemic animals is due to the effect of hypoglycemic state on the release of gonodotrophins from hypothalamus. Kumar and Saxena (2010) [8] , Suggested that the reduced concentration of glucose and insulin in blood were associated with nutritional anoestrus.…”
Section: Phosphorus (Mg/dl)mentioning
confidence: 99%
“…Ahmed et al [38] reported 9.07±0.10 mg/dl in delayed buffalo heifers. Also lower concentration of inorganic phosphorus reported in acyclic Murrah buffaloes [42], anestrous buffaloes [43,35].…”
Section: Group IVmentioning
confidence: 96%